2019
DOI: 10.1177/1747519819861389
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aryl-substituted quinolines and tetrahydroquinolines through Suzuki–Miyaura coupling reactions

Abstract: The synthesis and characterization of substituted (trifluoromethoxy, thiomethyl, and methoxy) phenyl quinolines is described. Dichlorobis(triphenylphosphine)palladium(II)-catalyzed Suzuki–Miyaura cross-coupling of 6-bromo- and 6,8-dibromo-1,2,3,4-tetrahydroquinolines, 5-bromo-8-methoxyquinoline, and 5,7-dibromo-8-methoxyquinoline with substituted phenylboronic acids affords the corresponding 6-aryl- (13a–d), 6,8-diaryl- (14a–c), 5-aryl- (15), and 5,7-diaryl- (16b, c) tetrahydroquinolines and quinolines in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 47 publications
(63 reference statements)
0
23
0
1
Order By: Relevance
“…(3) and 6,8-dibromoquinoline (4) treated with NaOMe or CuCN were synthesized according to our reported procedures. [14,39] Furthermore, the synthesis of 5,7-dibromo-8-hydroxyquinoline (17) and 5,7-dibromo-8-methoxyquinoline (19) via bromination of 8hydroxyquinoline (15) and 8-methoxyquinoline (16), respectively, was reported in our recent works. [40,55] The isolated compounds, 2-10, 12-14, and 17-19, were fully characterized by melting point, HRMS analysis, infrared, 1 H, 13 C, HMBC (heteronuclear multiple bond correlation), and HETCOR spectroscopy in these papers.…”
Section: The Synthesis Of Substituted Quinoline Compoundsmentioning
confidence: 92%
See 2 more Smart Citations
“…(3) and 6,8-dibromoquinoline (4) treated with NaOMe or CuCN were synthesized according to our reported procedures. [14,39] Furthermore, the synthesis of 5,7-dibromo-8-hydroxyquinoline (17) and 5,7-dibromo-8-methoxyquinoline (19) via bromination of 8hydroxyquinoline (15) and 8-methoxyquinoline (16), respectively, was reported in our recent works. [40,55] The isolated compounds, 2-10, 12-14, and 17-19, were fully characterized by melting point, HRMS analysis, infrared, 1 H, 13 C, HMBC (heteronuclear multiple bond correlation), and HETCOR spectroscopy in these papers.…”
Section: The Synthesis Of Substituted Quinoline Compoundsmentioning
confidence: 92%
“…[13][14][15] Many studies about pharmacological features of aryl or nitro/ amino-substituted quinolines have been interested due to that they have been starting materials for bioactive polycyclic systems. [16,17] Nitrated derivatives, which exhibit biological potency, that is, antileishmanial [18] or potent mutagenic activities, [19] are important key compounds for the preparation of amino derivatives for pharmacological use. [16,20] The aryl-substituted quinolines displayed a high antipesticide activity against the nematode Haemonchus contortus, [21] agricultural predatory activity, significant antibacterial activity, [22] anti-inflammatory, analgesic, antipyretic activities, and efficient inhibition of the COX-2 enzyme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Cyano substituted 8-hydroxyquinolines were synthesized by metal-assisted substitution reaction according to our reported procedures. [3,22,26] Furthermore, the synthesis of 6,8-diphenylquinoline (12) via Suzuki coupling was also reported in our recent works. [26,30] The isolated compounds 2-5, 7, 11, and 12 were fully characterized by melting point, HRMS analysis, infrared, 1 H, 13 C, heteronuclear multiple bond correlation, and heteronuclear correlation nuclear magnetic resonance (NMR) spectroscopy in those papers.…”
Section: Synthesis Of the Substituted Quinoline Compoundsmentioning
confidence: 70%
“…In our previous publications, we showed that bromination is an easy functionalization method for quinolines starting from tetrahydroquinoline and the brominated tetrahydroquinolines and quinolines were transformed to their respective derivatives. [1,9,24,26] In our recent studies, brominated quinolines were synthesized according to reported procedures starting from 1,2,3,4-tetrahydroquinoline and 8-substituted quinoline. [8,9,[27][28][29] The brominated quinoline and tetrahydroquinolines were converted to a series of corresponding methoxy-, [1,9] cyano-, [9,24] silyl-, [9] thiomethyl-, [9] hydroxyl-, [29] and phenyl- [26] substituted derivatives of quinolines (∼60 analogs) by metal-assisted substitution reactions and Suzuki-Miyaura crosscoupling reactions.…”
Section: Introductionmentioning
confidence: 99%